2014
DOI: 10.1109/tie.2013.2251740
|View full text |Cite
|
Sign up to set email alerts
|

Analyses on Electromagnetic and Temperature Fields of Superhigh-Speed Permanent-Magnet Generator With Different Sleeve Materials

Abstract: In this paper, a superhigh-speed permanent-magnet generator (SHSPMG) which has an alloy sleeve on the rotor outer surface is investigated. The purpose of the sleeve is to fix the permanent magnets and protect them from being destroyed by the large centrifugal force. However, the sleeve material characteristics have much influence on the superhigh-speed machine, and therewith, most of rotor eddy-current losses are generated in the alloy rotor sleeve, which could increase the device temperature. Taking a 117-kW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…In Eqs. (7) and (8), s is the change in radius of the segment and ds is the change in the radial dimension, as indicated in Figure 5. To maintain compatibility:…”
Section: Thick Walled Cylinder or Disk Analysismentioning
confidence: 99%
“…In Eqs. (7) and (8), s is the change in radius of the segment and ds is the change in the radial dimension, as indicated in Figure 5. To maintain compatibility:…”
Section: Thick Walled Cylinder or Disk Analysismentioning
confidence: 99%
“…One key problem of the rotor eddy current loss attenuation, which relates to the rotor temperature rise, is unique to these types of machine because of the poor heat dissipation environment of the rotor and large current harmonics under voltage-source inverter (VSI) supply. Researchers found that a conductive sleeve over the rotor can reduce the eddy current losses (ECLs) significantly, and a great deal of research has been conducted into the performance of different configurations and structure parameters [1][2][3][4]. Meanwhile, continuous efforts have been devoted to the harmonic suppression algorithm of the currents produced by VSI [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Copper plating, has high conductivity, and the advantages of copper sleeves in reducing eddy-current losses was presented [14,15], and the influence of copper layer thickness on rotor eddy-current losses and temperature distribution was analyzed. In [16], the electromagnetic and temperature fields of machine with different sleeve materials were researched.…”
Section: Introductionmentioning
confidence: 99%